Enhancing Hotel Service Quality: Design and Implementation of WiFi Coverage - Wang, Ping; Yang, Yue (Journal of Computer Science and Software Applications, 2024)
Hotels serve as temporary accommodations for individuals traveling for leisure or work. Guests increasingly expect reliable internet access for activities such as leisure and entertainment, information retrieval, email communication, and telecommuting. Consequently, a robust internet infrastructure has become a crucial criterion for evaluating a hotel's service quality. This paper examines the current state of hotel internet provisions and the corresponding demand, and it details the design and implementation of a hotel WiFi coverage strategy. The use of the common IEEE 802.11b standard access point (AP) is emphasized to ensure system scalability. This approach not only addresses the deficiencies in service quality associated with outdated hotel networks but also allows for considerable flexibility in future network upgrades.